Status of landslides and influencing factors in Bao Yen district, Lao Cai province and Quan Hoa district, Thanh Hoa province: A community-based survey - Kieu Thi Duong; Bui Xuan Dung; Tran Thi Dang Thuy; Nguyen Thi Thanh An; Ngo Tai Anh; Nguyen Duc Phuong (Journal of Forestry Science and Technology, 2025)
This study aimed to evaluate the status of landslide incidents and the factors influencing them in two mountainous districts: Quan Hoa (Thanh Hoa province) and Bao Yen (Lao Cai province). The primary method was used by random interviews with selective sampling of local residents and officials in areas frequently affected by landslides. Additionally, the Analytic Hierarchy Process (AHP) method was employed to assess the importance of influencing factors. The main findings showed that in Quan Hoa, over the past five years from 2020 to 2024, there were 36 landslide incidents, occurring along road embankments, in areas with steep slopes, or regions lacking vegetation cover. Similarly, in Bao Yen district, 36 landslide incidents were recorded over the same period. The AHP analysis revealed the order of importance of factors affecting landslides in both areas, from most to least significant, as follows: heavy and prolonged rainfall (A, 42.7%), high and steep terrain (B, 25.0%), overexploitation of resources (C, 10.6%), low vegetation cover with weak soil protection (F, 7.0%), inappropriate agricultural practices (D, 5.7%), improper construction of infrastructure (E, 5.2%), and changing meteorological factors due to climate change (G, 3.7%). Based on these findings, existing local measures and community feedback, the study proposed a comprehensive set of solutions focusing on land management, resource mobilization, and infrastructure reinforcement to mitigate landslide risks and minimize their impacts in these high-vulnerability upland regions.